2018
DOI: 10.1093/cz/zoy065
|View full text |Cite
|
Sign up to set email alerts
|

Wormlions prefer both fine and deep sand but only deep sand leads to better performance

Abstract: Wormlions are small fly larvae that dig pits in loose soil to trap their prey. Similar to other trapbuilding predators, like spiders and antlions, they depend on the habitat structure for successful trap construction and prey catch. We examined whether sites at which wormlions are present differ in sand depth and particle size from nearby sites, at which wormlions are absent. Next, in the laboratory we manipulated both sand depth and type (fine vs. coarse) to determine their joint effect on microhabitat prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Wormlions moved more and over longer distances in shallow sand, constructed smaller pits in it, and moved to deep sand when a choice was given. This finding strengthens our previous suggestion that shallow sand is considered unfavourable for pit-building predators 61 , either because smaller pits must be constructed or due to slower response to prey there. Direct light is also unfavourable, and wormlions avoided it in our experiment and constructed smaller pits there.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Wormlions moved more and over longer distances in shallow sand, constructed smaller pits in it, and moved to deep sand when a choice was given. This finding strengthens our previous suggestion that shallow sand is considered unfavourable for pit-building predators 61 , either because smaller pits must be constructed or due to slower response to prey there. Direct light is also unfavourable, and wormlions avoided it in our experiment and constructed smaller pits there.…”
Section: Discussionsupporting
confidence: 90%
“…There was no difference in wormlion body mass among any treatments within each experiment (P > 0.64). The movement distance of each wormlion was estimated by dividing the test arena into 100 equal squares and counting the number of squares traversed by the wormlions (similar to 61 ). We used this method rather than following wormlion movement, because when wormlions move over long distances, newer tracks cross the older ones, hindering an exact estimation of movement distance.…”
Section: Methodsmentioning
confidence: 99%
“…Second, large wormlions remained either under shade or in deep sand, while small ones relocated more frequently to lit or shallow sand areas. The advantage deep sand provides for large individuals is much greater than for small individuals 61 , as demonstrated in the interactive effect of wormlion size and sand depth on pit area (Fig. 3 c).…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have demonstrated wormlion preference for fine-textured loose soil, deep and dry sand, and shade 57 59 . The shade is preferred in order to avoid exposure to high temperature and desiccation 60 , while deep sand enables the construction of larger pits, which in turn improve prey capture 61 . Similar to other TB predators, wormlions compete over suitable sites in which to construct their traps, and the outcome of the competition for the loser is either to settle in an inferior microhabitat or to construct a smaller pit-trap 52 , 58 .…”
Section: Introductionmentioning
confidence: 99%
“…1 A) is a pit-building ambush predator (Franks et al 2019). The hunting success of it largely depends on the abiotic factors of its habitat (Scharf and Ovadia 2006; Bar-Ziv et al 2019), such as sand grain size and distribution, and the majority of antlion species prefer sand with a comparably small particle size (Allen and Croft 1985; Loiterton and Magrath 1996; Botz et al 2003; Farji-Brener 2003). Suitable substrates will enable the construction of considerably larger pits (Barkae et al 2012), resulting in the ability to capture larger prey and reducing the risk of prey escapes (Griffiths 1980; Lucas 1982; Heinrich and Heinrich 1984; Scharf et al 2018).…”
Section: Introductionmentioning
confidence: 99%